Rasch models in health - Christensen, Karl Bang; Kreiner, Svend; Mesbah, Mounir (London : ISTE Ltd. ; Hoboken, NJ : John Wiley & Sons, 2013)
""The family of statistical models known as Rasch models started with a simple model for responses to questions in educational tests presented together with a number of related models that the Danish mathematician Georg Rasch referred to as models for measurement. Since the beginning of the 1950s the use of Rasch models has grown and spread from education to the measurement of health status. This book contains a comprehensive overview of the statistical theory of Rasch models."
Probabilistic models. The Rasch model for dichotomous items / Svend Kreiner -- Rasch models for ordered polytomous items / Mounir Mesbah, Svend Kreiner -- Inference in the Rasch model. Estimation of item parameters / Karl Bang Christensen -- Person parameter estimation and measurement in Rasch models / Svend Kreiner, Karl Bang Christensen -- Checking the Rasch model. Item fit statistics / Karl Bang Christensen, Svend Kreiner -- Overall tests of the Rasch model / Svend Kreiner, Karl Bang Christensen -- Local dependence / Ida Marais -- Two tests of local independence / Svend Kreiner, Karl Bang Christensen -- Dimensionality / Mike Horton, Ida Marais, Karl Bang Christensen -- Applying the Rasch model. The polytomous Rasch model and the equating of two instruments / David Andrich -- A multidimensional latent class Rasch model for the assessment of the health-related quality of life / Silvia Bacci, Francesco Bartolucci -- Analysis of rater agreement by Rasch and IRT models / Jürgen Holm Petersen -- From measurement to analysis / Mounir Mesbah -- Analysis with repeatedly measured binary item response data by Rasch scales / Volkert Siersma, Paolo Eusebi -- Creating, translating and improving Rasch scales -- Writing health-related items for Rasch models -- patient-reported outcome scales for health sciences: from medical paternalism to patient autonomy / John Brodersen, Lynda C Doward, Hanne Thorsen, Stephen P Mckenna -- Adapting patient-reported outcome measures for use in new languages and cultures / Stephen P Mckenna, Jeanette Wilburn, Hanne Thorsen, John Brodersen -- Improving items that do not fit the Rasch model / Tine Nielsen, Svend Kreiner -- Analyzing and reporting Rasch models -- Software for Rasch analysis / Mounir Mesbah -- Reporting a Rasch analysis / Thomas Salzberger.
Includes bibliographical references and index.
Online resource; title from digital title page (ebrary, viewed on December 23, 2014).
Keywords: Rasch models; Medicine -- Research -- Statistical methods; Models, Statistical; Statistics as Topic; Health Surveys -- statistics & numerical data; MEDICAL -- Research; Medicine -- Research -- Statistical methods; Rasch models; Electronic books